Validação de métodos analíticos para quantificação de enrofloxacino em comprimidos palatáveis - Rebouças, Camila Tavares [UNESP] (2014)
Enrofloxacin, a second generation fluoroquinolone derivative of nalidixic acid, developed in the 80's, was the first fluoroquinolone introduced in veterinary medicine for the treatment of various bacterial infections. There are several published studies in literature that describe analytical methods for enrofloxacin in pharmaceutical dosage forms, but a few for tablets. Most of them are related to high performance liquid chromatography (HPLC) using mobile phases constituted by buffer solutions, which may damage the chromatographic columns over time, or methods that involve, mostly, the use of large amounts of organic solvents. In this way, this study aimed to develop new analytical methods for the analysis of enrofloxacin in tablets, which have the lowest impact on the environment as possible and that be more convenient, safer for operators and more economical than the analytical methodologies already described for enrofloxacin. Enrofloxacin was analyzed qualitatively in relation to moisture content, solubility and melting range. Furthermore, it was performed an analysis by infrared spectroscopy and was developed a stability indicative method by thin layer chromatography (TLC). Regarding the quantitative analysis, it was validated HPLC methodology with PDA detection at 278 nm, mobile phase composed by aqueous 5% acetic acid and methanol (75:25 v/v), the concentration range from 6.0 to 14.0 μg/mL, accuracy of 100.14%, content of 100.94% and average retention time of 5.1 minutes; microbiological assay by turbidimetric method, in the concentration range from 4.0 to 8.0 μg/mL, using Staphylococcus epidermidis ATCC 12228, with average accuracy of 100.01% and 97.84% of content; and infrared spectroscopy, in the concentration range from 1.0 to 3.0 mg/150 mg, 98.00% of accuracy and content of 99.74%. Validation of the methods was conducted according to ICH guidelines and Brazilian legislation. The developed methods showed no statistical ...